Evaluation of sample treatment for simultaneous flow injection hydride generation and determination of As, Bi, Sb and Se by GFAAS - Freschi, Carolina D. [UNESP]; Freschi, Gian Paulo G. [UNESP]; Gomes Neto, José A. [UNESP] (My University, 2004)
A new method was developed for the simultaneous determination of As, Bi, Sb, and Se by flow injection hydride generation graphite furnace atomic absorption spectrometry. An alternative two-step sample treatment procedure was used. The sample was heated (80°C) for 10 min in 6 M HCl to reduce Se(VI) to Se(IV), followed by the addition of 1% (m/v) thiourea solution to reduce arsenic and antimony from the pentavalent to the trivalent states. With this procedure, all analytes were converted to their most favorable and sensitive oxidation states to generate the corresponding hydrides. The pre-treated sample solution was then processed in the flow system for in situ trapping and atomization in a graphite tube coated with iridium. The Ir permanent modifier remained stable up to 300 firings and new coatings were possible without significant changes in the analytical performance. The accuracy was checked for As, Bi, Sb, and Se determination in water standard reference materials NIST 1640 and 1643d and the results were in agreement with the certified values at a 95% confidence level. Good recoveries (94-104%) of spiked mineral waters and synthetic mixtures of As(III), As(V), Sb(III), Sb(V), Se(VI), and Se(IV) were also found. Calculated characteristic masses were 32 pg As, 79 pg Bi, 35 pg Sb, and 130 pg Se, and the corresponding limits of detection were 0.06, 0.16, 0.19, and 0.59 μg L-1, respectively. The repeatability for a typical solution containing 5 μg L-1 As, Bi, Sb, and Se was in the 1-3% range.